Silicone tags as an effective method of monitoring environmental contaminant exposures in a geographically diverse sample of dogs from the Dog Aging Project - Matheson, Rylee; Sexton, Courtney L.; Wise, Catherine F.; O’Brien, Janice; Keyser, Amber J.; Kauffman, Mandy; Dunbar, Matthew D., DAP Consortium; Akey, Joshua M.; Benton, Brooke; Borenstein, Elhanan; Castelhano, Marta G.; et al. (Frontiers in Veterinary Science, 2024)
Companion animals offer a unique opportunity to investigate risk factors and exposures in our shared environment. Passive sampling techniques have proven effective in capturing environmental exposures in dogs and humans. In a pilot study, we deployed silicone monitoring devices (tags) on the collars of a sample of 15 dogs from the Dog Aging Project Pack cohort for a period of 120 hours (5 days). We extracted and analyzed the tags via gas chromatography-mass spectrometry for 119 chemical compounds in and around participants' homes. Analytes belonging to the following chemical classes were detected: brominated flame retardants (BFRs), organophosphate esters (OPEs), polycyclic aromatic hydrocarbons (PAHs), polychlorinated biphenyls (PCBs), pesticides, phthalates, and personal care products. The types and amounts of analytes detected varied substantially among participants. Data from this pilot study indicate that silicone dog tags are an effective means to detect and measure chemical exposure in and around pet dogs' households. Having created a sound methodological infrastructure, we will deploy tags to a geographically diverse and larger sample size of Dog Aging Project participants with a goal of further assessing geographic variation in exposures.